China Newspaper Directory - Strömberg, David; Qin, Bei; Wu, Yanhui (Stockholm University, 2018)
Comprehensive directory of approximately 1,000 general-interest Chinese newspapers from 1981 to 2011.

The newspaper directory is constructed from four data sources: (1) the Chinese Newspaper Directory (2003, 2006, 2010), published by the State Administration for Press and Publication (SPPA) -- the authority that issues newspaper licenses; (2) the Annual China Journalism Yearbooks (1982-2011), published by the Chinese Academy of Social Science; (3) the China Newspaper Industry Yearbooks (2004-2011), published by a Beijing-based research institute; and (4) an eight-volume collection of the front pages of major newspapers on the date of first publication.

Description of the variables in the data set:

1.    Province, prefecture, and county are the location of the headquarter of a newspaper.
2.    newspaper_id: a numerical identifier for each newspaper
3.    license_id: a numerical identity for a newspaper’s license issued by the Chinese National Press and Publication Administration. Typically, when a newspaper changes its name, its license remains the same and so does the license_id variable.
4.    newspaper_ch: the Chinese name of a newspaper
5.     newspaper_en: the English translation of the Chinese name of a newspaper
6.    Previous_name: the previous name of a newspaper if the newspaper ever changes names
7.    Supervisor: the direct supervisory organization of a newspaper
8.    Supervisor_type: the type of the supervisor of a newspaper, classified into one of the following categories
-    Party: the supervisor is a CCP committee
-    Government agency: the supervisor is a government department
-    Mass organization: the supervisor is a mass organization, such as a professional association
-    Nonnewspaper media: the supervisor is a non-newspaper media such as a broadcaster
-    Parent newspaper: the supervisor is a newspaper that owns the newspaper
-    Party media group: the supervisor is a media group supervised by a CCP committee
-    Soe: the supervisor is a state-owned enterprise
9.    Head_unit: the unit that manages the newspaper. Most of the time, the head unit of a newspaper is the same as its supervisor. In some cases, the supervisor (e.g., a CCP committee) may delegate power to an organization (e.g., a party newspaper) to manage a newspaper.
10.    Admin_rank: the administrative rank of a newspaper, classified as “central”, “province”, “capital city (of a province)”, “prefecture (non-capital-city prefecture” and “county.”
11.    Ownership: residual claimant of a newspaper
12.     Founded_date: the date when a newspaper is founded.
13.    Republish_date: the date when a newspaper is republished after a period of suspension.
14.    Termination_date: the date when a newspaper is terminated.
15.    Category_content: is the content type of a newspaper, classified as one of the following categories:
-    Daily: a general party daily, i.e., the mouthpiece of a CCP committee
-    Evening: a newspaper whose title contains the words “evening newspaper”, typically quasi-commercialized general-interest newspaper and published in the afternoon
-    Metro: commercial general interest newspaper published in the morning
-    Digest_general: a general interest digest, which does not publish original articles
-    Mixed_econ: a semi-general interest newspaper with a focus on economic news
-    Mixed_politics: a semi-general interest newspaper with a focus on political news
-    Mixed_law: a semi-general interest newspaper with a focus on legal issues
-    Mixed_life: a semi-general interest newspaper with a focus on the coverage of life style
Keywords: Media and Communications; Medie-, kommunikations-, och informationsvetenskaper